(untitled) (UUM Journal of Legal Studies, 2025)
Sharie lawyers represent disputing parties in resolving their problems in Shariah courts. In Malaysia, the laws applicable to regulate the affairs of Shariah lawyers in terms of admission, qualifications and disciplinary matters are determined by state rules established based on the Islamic Religious Administration Enactment of the states or the Shariah Court Enactment of the states. For Penang, the applicable law is the Rules of Sharie Lawyers or Peguam Sharie (State of Penang) 1997. Therefore, the Penang Islamic Religious Council (MAINPP) is responsible for regulating Sharie lawyers in Penang. However, to date, there are still significant loopholes in this law that have disrupted its regulatory process. As a result, the profession of Sharie lawyer faces daily challenges, including inconsistent admission criteria, lack of clear disciplinary procedures, limited professional development, jurisdictional confusion, enforcement issues, and eroding public trust. The present research objective is to analyze loopholes in the Peguam Sharie (State of Penang) Rules 1997, identify areas of weakness, and propose recommendations for improving the regulatory framework for Sharie lawyers in Penang. A qualitative approach was used in this study and the data collection was done using primary and secondary sources. For primary sources, the researchers conducted interview sessions with Penang Sharie lawyers and Penang Shariah Judiciary Department (JKSNPP) officers in order to obtain firsthand perspectives, context, clarity, validation, and recommendations for the research. Whereas, for secondary sources, the researchers referred to journals, books, and proceedings, as well as electronic database sources. The data was analyzed using a content analysis method. This research found that there were eight provisions that needed to be reformed to improve the profession of Sharie lawyers in Penang. This research has suggested an amendment to the Peguam Syarie (State of Penang) Rules, 1997. It has also recommended that the parties involved in the practice of Shariah law in Penang be made aware of the challenges faced and amend the existing law so that the profession of Sharie lawyers remains relevant in the future.